Methodological issues and challenges in research on mathematics textbooks - Rezat, Sebastian; Sträßer, Rudolf (NOMAD Nordic Studies in Mathematics Education, 2015)
The growing field of research on mathematics textbooks can be divided into three areas: 1) Research that focuses on the influences on textbooks; 2) Research that focuses on the mathematics textbook itself; 3) Research on the use of mathematics textbooks and its impact. Concentrating on research done in the Nordic countries, the paper provides an overview of methods used in all three areas. Based on an analysis of 24 papers, the findings are that whereas research related to area 1) and 2) usually relies on surveys or content analysis of textbooks – well-established methods from the social sciences –, research in area 3) has to face the methodological challenges of gathering valid data and of generalization of its results. Triangulation and typologies are presented as possible ways to tackle these challenges.